Frequency and risk factors of surgical recurrence of Crohn’s disease after primary bowel resection - Zhou, Jiajie; Li, Yi; Gong, Jianfeng; Zhu, Weiming (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: The purpose of this study was to evaluate the frequency and risk factors associated with Crohn’s disease (CD) reoperation after primary bowel resection. Materials and Methods: We identified 166 patients suffering from CD with primary bowel resection and primary anastomosis from the clinical database of a university hospital. The cumulative recurrence rate and median recurrence-free survival (RFS) were calculated using the Kaplan-Meier analysis. Categorical variables were compared using a log-rank test. A Cox proportional hazard model was used for multivariate analysis. Results: The median age of reoperation was 30 years, and the median RFS was 30 months. The reoperation intervention rate was 16.9%. It was shown that smoking (p=0.015) and jejunoileal anastomosis (p=0.002) were significantly closely correlated to an increased risk of surgical recurrence, whereas laparoscopy (p=0.039), side-to-side anastomosis (p=0.018), and anastomotic stoma wider than 3 cm (p=0.024) were significantly closely correlated to a reduced risk of surgical recurrence. Conclusion: This study provided a robust result that smoking and small intestinal lesions were the risk factors of surgical recurrence for patients with CD upon the initial gut resection. Laparoscopy, side-to-side anastomosis, and wide anastomotic stoma were found to be protective factors against surgical recurrence. Cite this article as: Zhou J, Li Y, Gong J, Zhu W. Frequency and risk factors of surgical recurrence of Crohn’s disease after primary bowel resection. Turk J Gastroenterol 2018; 29: 655-63.